Amaryllidaceae alkaloids in skin cancer management: Photoprotective effect on human keratinocytes and anti-proliferative activity in melanoma cells (2023)
Skin cancer has high rates of mortality and therapeutic failure. In this study, to develop a multi-agent strategy for skin cancer management, the selective cytotoxicity of several alkaloid fractions and pure alkaloids isolated from Amaryllidaceae species was evaluated in melanoma cells. In addition, UVB-stimulated keratinocytes (HaCaT) were exposed to seven alkaloid fractions characterized by GC-MS, and the production of intracellular reactive oxygen species (ROS) and IL-6, were measured to evaluate their photoprotection effects. The Eucharis caucana (bulb) alkaloid fraction (20 μg/ml) had a clear effect on the viability of melanoma cells, reducing it by 45.7% without affecting healthy keratinocytes. This alkaloid fraction and tazettine (both at 2.5 μg/ml) suppressed UVB-induced ROS production by 31.6% and 29.4%, respectively. The highest anti-inflammatory potential was shown by the Zephyranthes carinata (bulb) alkaloid fraction (10 μg/ml), which reduced IL-6 production by 90.8%. According to the chemometric analysis, lycoramine and tazettine had a photoprotective effect on the UVB-exposed HaCaT cells, attenuating the production of ROS and IL-6. These results suggest that Amaryllidaceae alkaloids have photoprotective and therapeutic potential in skin cancer management, especially at low concentrations.